Alternative Design of a Pneumatic Conveying Machine for Rice Husk as A Coal Substitute for Rotary Kiln Fuel in Cement Factories - Permanadewi, Indrasukma; Febry Ibrahim, Ahmad; Azzahra Putri Solihin, Syifa; Aldiansyah, Rizky (Universitas Negeri Semarang, 2024)
The reduced amount of coal transported to cement factories is being diverted to rice husk, which is biomass, to facilitate the use of increasingly expensive coal. This transition is necessary due to the different characteristics of rice husk compared to coal. Additionally, the combustion process in rotary kilns requires extremely high temperatures (1,400–1,500°C). However, a significant portion of the generated energy is lost through the kiln walls, exhaust gases, and heat radiation. These heat losses reduce thermal efficiency and increase fuel consumption. Coal, fuel oil, and natural gas are the primary energy sources for cement kilns, which are not only expensive but also have negative environmental impacts. The fluctuation in fossil fuel prices further affects overall cement production costs. To address these challenges, cement factories must design an efficient rice husk conveying system from storage to the rotary kiln. Transporting rice husks with air ensures no unintended reactions while allowing smooth flow through closed horizontal and vertical transport pipes commonly used in the industry. This study aims to design a pneumatic conveying machine with a closed air pressure system to transport biomass (rice husks) at a capacity of 7 tons/hour as an alternative fuel for rotary kilns in the cement industry. The design method follows several stages, including practical work experience, literature review, material selection, design considerations, conceptual design, calculations, and technical drawings. The proposed system utilizes the dilute phase method, with a blower power of 49.26523 kW pushing the rice husks toward the hopper. The pipeline flow parameter, measured as the pressure drop, is 132.9673 kPa. The selected materials include galvanized iron pipes with two elbows to connect horizontal and vertical sections.